Physicochemical characteristics of Moringa peregrina seeds and oil obtained by solvent and cold-press extraction - A. Jafari; M. Moslehishadb; Z. Ghanavi (Grasas y Aceites)
This study evaluated the quality of oil extracted from Moringa peregrina (MP) seeds. The seeds oil was extracted by Soxhlet and cold-press methods and named MPSO and MPCO, respectively. The physicochemical properties of the extracted oil were determined and the results showed that the Soxhlet technique had higher extraction efficacy than the cold-press technique (41.24 % vs. 22.5 %). In general, MPSO had higher acidity, oxidative stability, smoke point, and refractive index, with lower peroxide, iodine index, Cox index, and density than MPCO (p < 0.05). The antioxidant activity of MPSO was higher than MPCO (19.36 % vs. 12.88 %) (p < 0.05). In general, oleic acid and palmitic acid were found to be prominent in both samples with a 78 % omega-9 fatty acid content. The most abundant sterol compounds in the MP oil were stigmasterol, Δ5-avenasterol, and campesterol. In addition, γ-, α- and, δ-tocopherol were the most abundant tocopherols, respectively.